2014
DOI: 10.1146/annurev-arplant-050213-040054
|View full text |Cite
|
Sign up to set email alerts
|

Nonstructural Carbon in Woody Plants

Abstract: Nonstructural carbon (NSC) provides the carbon and energy for plant growth and survival. In woody plants, fundamental questions about NSC remain unresolved: Is NSC storage an active or passive process? Do older NSC reserves remain accessible to the plant? How is NSC depletion related to mortality risk? Herein we review conceptual and mathematical models of NSC dynamics, recent observations and experiments at the organismal scale, and advances in plant physiology that have provided a better understanding of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
580
2
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 617 publications
(610 citation statements)
references
References 150 publications
23
580
2
5
Order By: Relevance
“…Chemical analyses of the 6136 leaf samples indicated extremely wide-ranging concentrations of NSC, from 16.5% to 84.5% of total leaf mass (Table 3). Parallel to the spectra, this NSC range approximately meets the range reported for live, fresh foliar material worldwide [1,5,9]. Based on this range of chemical values, the PLSR analyses indicated that NSC can be estimated at the leaf level from reflectance with high precision (mean R 2 = 0.73 ± 0.06) and accuracy (average %RMSE = 12.9%) ( Table 3).…”
Section: Leaf-level Performancesupporting
confidence: 61%
“…Chemical analyses of the 6136 leaf samples indicated extremely wide-ranging concentrations of NSC, from 16.5% to 84.5% of total leaf mass (Table 3). Parallel to the spectra, this NSC range approximately meets the range reported for live, fresh foliar material worldwide [1,5,9]. Based on this range of chemical values, the PLSR analyses indicated that NSC can be estimated at the leaf level from reflectance with high precision (mean R 2 = 0.73 ± 0.06) and accuracy (average %RMSE = 12.9%) ( Table 3).…”
Section: Leaf-level Performancesupporting
confidence: 61%
“…The extent to which the formation of C reserves is an active process is a current matter of discussion (see reviews by Hoch in press; Palacio et al 2014;Dietze et al 2014). There is evidence that even under severe stress conditions, C reserves are never fully depleted (Gruber et al 2012;Hartmann et al 2013;Klein et al 2014) and that reserve storage may, in certain cases, be favored at the expense of growth (Wiley et al 2013;Saffell et al 2014).…”
Section: The Phenology Of Carbon and Nitrogen Reservesmentioning
confidence: 99%
“…In this context, the phenology of non-leafy organs (i.e., reproductive structures, wood, fine roots) has often been ignored in TEMs and, when represented, defined relative to that of leaves, despite an increasing amount of evidence that suggests there are not simple links between the phenologies of tree organs. The phenologies of non-leafy organs clearly deserve proper characterization, as there is increasing evidence that the growth of tree organs does not solely depend on the fueling of carbon from the canopy but, rather, is at least transitorily an active process modulated by seasonal variations in the ability of the organ to grow (Fatichi et al 2014;Dietze et al 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neutral red dye, widely used for observation of live or dead cells, has the potential to discriminate the contents of vacuoles, such as starch, which is the main component of power reserve, as cells radial parenchyma are and structural carbon source (CHANTUMA et al, 2007, DIETZE et al, 2014. For this reason it can be easily used to characterize necrosis of exchange of tissues when the plants are faced with forest fi re situations (DICKINSON; JOHNSON, 2004), or heat stress caused by solar scalds or intense cold (MANION, 1991;TATTAR, 1989).…”
Section: Resultsmentioning
confidence: 99%